Predicting Future Cash Flows: Does Cash Flow have Incremental Information over Accrual Earnings? / Tho Lai Mooi - Tho, Lai Mooi (UPENA, 2007)
Financial Reporting Standard No. 107 on cashflow statements in propagating the preparation of cash flow statements as an integral part of an entity's financial statements, has asserted that 'cash flow information is useful in assessing the ability of enterprise to generate cash and cash equivalents...' This study attempts to test this claim by investigating the predictive ability of cash flow from operations versus accrual accounting based data to forecast future cashflow from operations, using multivariate regression models and panel data on a sample of 173 firms listed on Bursa Malaysia. Three predictor variables, net income before extraordinary items (NI), NI plus depreciation and amortisation (NDA) and cash flow from operations (CFO) are used to forecast future cash flows from operations for the period from 1997 to 2005. This study has provided evidence that cashflow from operations data do have incremental predictive ability over accrual measures ofNI and NDA as indicated by the significant Beta coefficients of CFOs in all the eight regression models used. The predictive ability of all the regression models improves as more years of historical data of predictors are incorporated. The results also show that the accrual predictor of NDA is superior over NI in models that use only one or two years data. However, as more than two years data are used, the superiority of NDA over NI disappears.